PEMETAAN POTENSI WILAYAH UNTUK MENUNJANG KEBIJAKAN PANGAN KABUPATEN PACITAN - Burhanudin Mukhamad Faturahman (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2017)
This study aims to provide advice in the form of mapping the area for the development of food policy in Pacitan Regency. Research results through secondary data collection technique of the Central Bureau of statistics the next Pacitan Regency analyzed using techniques scalling indicates that food sweet potato is very well developed in the subdistrict include Donorojo, Pacitan Punung, Pacitan, Pringkuku, Kebonagung, Arjosari, Nawangan, Bandar, Tegalombo and Tulakan. Local government development policy has led to an increase in the food had not yet led to an increase in the availability of plant sweet potatoes along with a town developed. Therefore, the local government needs to devise a policy of pacitan Regency foodstuffs suitable potential regions match the characteristics of the region.